Implementation of ISMUBA learning in shaping islamic character at SMK Muhammadiyah Bangunjiwo Bantul Yogyakarta - Joni Mukti Wibowo; Sutarman (At Turots: Jurnal Pendidikan Islam, 2023)
This research was motivated by the rise of crime cases that occurred in the community such as brawls, clitics and theft, so the authors raised the theme of ISMUBA learning in shaping the Islamic character of class X students at SMK Muhammadiyah Bangunjiwo. Bantul Yogyakarta The research method used in this research is qualitative with field research. Data collection techniques using interviews, observation and documentation. Then data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions. As for checking the validity of the data is done by triangulation of data sources. These results can be concluded that: First, the implementation of ISMUBA learning in the formation of Islamic character, namely by habituation carried out in class by reading prayers together, memorizing the Qur'an and memorizing hadiths, tadarus together and memorizing prayer readings. The implementation activities are also supported by the habituation carried out at school by praying Duha together, tahsin, murojaah and praying in congregation. Second, the supporting factors in forming Islamic character are the existence of facilities and infrastructure, Islamic habituation and competent teachers who support the learning process in forming students' Islamic character, while the inhibiting factor in implementing the formation of Islamic character of students is the lack of awareness that exists within students about the importance of character. Islamic education, lack of support and motivation from parents and the methods used are still monotonous. Third, the benefits in forming Islamic character in ISMUBA learning are getting closer to Allah, having a disciplined attitude, having an attitude of honesty and high courtesy and being liked by many people